PENGARUH PERBEDAAN PELARUT TERHADAP PROSES EKSTRAKSI BATANG SEREH (Cymbopogon citratus) - Miftahurrahmah, Miftahurrahmah; Nurmalasari, Enny; Putra, Reski Lediyo; Maulana, Ihsan; Chairunnisak, Aula (Politeknik ATI Padang, 2023)
The abundant benefits of essential oils have led to a significant increase in demand, prompting researchers to continuously explore this field to achieve optimal results. Various extraction methods can be employed to obtain essential oils. In this study, researchers used the maceration method with variations in several solvents as comparators. The resulting maceration filtrate was subsequently distilled to obtain pure essential oil, aiming to find an efficient process for essential oil production and identify the most suitable solvent for the production process. The solvents used were Methanol, Ethanol, n-Hexane, and Water. During the maceration method, a sample of 150 g lemongrass was prepared with a size of 1 cm and soaked in 1 L of solvent in a closed container for 24 hours. The filtrate was then distilled to obtain a pure product, which was further characterized using GC-MS. The research findings showed that essential oil was extracted most effectively by ethanol solvent, yielding 23.31 g, and the GC-MS analysis indicated that the lemongrass oil contained 25.75% Geraniol. It was concluded that Geraniol is more soluble in ethanol due to its closer polarity to the compounds within lemongrass oil, resulting in a higher yield compared to extractions using other solvents.